Marijuana Dependence: Not Just Smoke and Mirrors - Ramesh, Divya (2011)
Marijuana (Cannabis sativa) is the most commonly used illicit drug worldwide as well as in the Unites States. Prolonged use of marijuana or repeated administration of its primary psychoactive constituent, Δ(9)-tetrahydrocannabinol (THC), can lead to physical dependence in humans and laboratory animals. The changes that occur with repeated cannabis use include alterations in behavioral, physiological, and biochemical responses. A variety of withdrawal responses occur in cannabis-dependent individuals: anger, aggression, irritability, anxiety and nervousness, decreased appetite or weight loss, restlessness, and sleep difficulties with strange dreams. But the long half-life and other pharmacokinetic properties of THC result in delayed expression of withdrawal symptoms, and because of the lack of contiguity between drug cessation and withdrawal responses the latter are not readily recognized as a clinically relevant syndrome. Over the past 30 years, a substantial body of clinical and laboratory animal research has emerged supporting the assertion that chronic exposure to cannabinoids produces physical dependence and may contribute to drug maintenance in cannabis-dependent individuals. However, no medications are approved to treat cannabis dependence and withdrawal. In this review, we describe preclinical and clinical research that supports the existence of a cannabinoid withdrawal syndrome. In addition, we review research evaluating potential pharmacotherapies (e.g., THC, a variety of antidepressant drugs, and lithium) to reduce cannabis withdrawal responses and examine how expanded knowledge about the regulatory mechanisms in the endocannabinoid system may lead to promising new therapeutic targets.